Strategi Pemberdayaan UMKM Sektor Peternakan Ayam Organik (StudiPadaKoperasi Hidayah Sumatera Utara) - Latief Ilhamy; Sundari Pratiwi (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2018)
MSME (Micro, Small and Medium Enterprises) is one of the efforts that have the Indonesian government to reduce unemployment , poverty and income distribution . In Indonesia, SMEs dominate as much as 99 % ( percent ) and 1% for large businesses . SMEs have also been able to absorb significant workforce that is as much as 97 % . SME sector is also able to contribute around 56% of gross domestic product . For that I am interested in studying the issues related to SMEs SME sector is an organic chicken farm in Medan that is empowered by the Cooperative Hidayah SU . This research aims to ( 1 ) the role of cooperatives Untukmengetahui guidance to the SMEs sector in the field of organic chicken farms . ( 2 ) To determine what factors are causing failures organic chicken farm in Medan . ( 3 ) What steps are performed Cooperative Hidayah Medan in addressing the failure of the organic chicken farm.